2008
DOI: 10.1016/j.jssc.2008.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and activity of visible-light-driven TiO2 photocatalyst codoped with nitrogen and cerium

Abstract: Nitrogen and cerium codoped TiO 2 photocatalysts were prepared by a modified sol-gel process with doping precursors of cerium nitrate and urea, and characterized by X-ray diffraction (XRD), thermogravimetry-differential scanning calorimetry (TG-DSC), X-ray photoelectron spectra (XPS) and ultraviolet-visible light diffuse reflectance spectra (UV-vis DRS). Results indicate that anatase TiO 2 is the dominant crystalline type in as-prepared samples, and CeO 2 crystallites appear as the doping ratio of Ce/Ti reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(88 citation statements)
references
References 34 publications
2
84
1
1
Order By: Relevance
“…Therefore, co-doped samples show superior visible absorption compared with singly doped materials, due to the narrower band gap and multiple excitation processes [14]. The band gap energy (E b ) of these compounds can be estimated by the formula [6,29]: E b = 1,240/k g , where k g is the wavelength corresponding to the intersection point of the vertical and horizontal parts of the spectra. The values of band gap energy and absorption band are shown in Table 2 the same conditions, the percent degradation of MO degraded by pure TiO 2 , N(0.020)La(0.004)TiO 2 , N(0.020)-La(0.008)TiO 2 , and N(0.020)La(0.016)TiO 2 were 0, 48, 77, and 30%, respectively.…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…Therefore, co-doped samples show superior visible absorption compared with singly doped materials, due to the narrower band gap and multiple excitation processes [14]. The band gap energy (E b ) of these compounds can be estimated by the formula [6,29]: E b = 1,240/k g , where k g is the wavelength corresponding to the intersection point of the vertical and horizontal parts of the spectra. The values of band gap energy and absorption band are shown in Table 2 the same conditions, the percent degradation of MO degraded by pure TiO 2 , N(0.020)La(0.004)TiO 2 , N(0.020)-La(0.008)TiO 2 , and N(0.020)La(0.016)TiO 2 were 0, 48, 77, and 30%, respectively.…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…In order to further improve the photocatalytic activity, codoped titania with double non-metal [21][22][23][24][25][26], metal-non-metal [27][28][29][30], metal-metal ion [31,32] and metal-semiconductor [33] has attracted more attention. The codoped TiO 2 with rare-earth transition metal and non-metallic element has aroused great attention [34,35]. Some studies demonstrated that the codoping with transition metal and nonmetallic element could effectively modify the electronic structures of TiO 2 and shift its absorption edge to a lower energy [30].…”
Section: Introductionmentioning
confidence: 99%
“…The XPS C1s binding energy at 288 eV was attributed to carbonate species. [53] Urea as a nitrogen source has been employed in the preparation of "co-doped" TiO 2 with ions of B, [54] Ce, [55] Cu, [56] Nb, [57] and Pt. [58] The combination of urea and titanium dioxide was also investigated in a nonphotocatalytic context, like electrorheological properties, [59,60] nanocomposite electrodes for application in lithium ion batteries, [61] and new resins with high stability.…”
Section: Introductionmentioning
confidence: 99%